Senseless - Penelope Spheeris; Marlon Wayans; David Spade; Matthew Lillard; Rip Torn; Tamara Taylor; Brad Dourif; Richard McGonagle; Esther Scott; Debra Jo Rupp; Mark Christopher Lawrence; John Ingle; et al. (USA Dimension Films, 1998)
A student gets his senses enhanced by an experimental drug. But abuse is not an option.
Darryl Witherspoon is a young black college student who wants to win annual junior analyst competition, which can land him a job in a big brokerage company. He becomes a guinea pig for the drug developed at the college which is promised to heighten all senses by ten times.
Language(s): English, Turkish Subtitle(s): Turkish
Keywords: Comedy; Romance